PERSEPSI PENGUNJUNG TERHADAP KERATON KAIBON DI KOTA SERANG - Chotibul Umam (International Journal Mathla’ul Anwar of Halal Issues, 2022)
The purpose of this study is to determine the perception of visitors in the Kaibon palace in terms of tourist attractions and facilities. The type of research is descriptive, the population in this study are visitors in the Kaibon palace. The sample was determined as many as 100 people who were taken using non-probability sampling with convenience sampling technique. Data were collected by questionnaire and analyzed descriptively. The results of the study that 1) tourists' perceptions of the Kaibon palace were categorized as good in terms of the architectural uniqueness dimension with a total score of 4.05 2) tourists' perceptions of the Kaibon palace in terms of the garden landscape dimensions were categorized as adequate with a total score of 3.27 3) tourists' perceptions of the existence of the Kaibon palace in terms of the dimensions of the canals around the Kaibon palace was categorized as good with a total score of 3.67 4) tourists' perceptions of the Kaibon palace were categorized as good in terms of the handicraft dimension with a total score of 3.95 5) tourists' perceptions of the Kaibon palace in terms of the culinary dimensions were categorized good with a total score of 3.89 6) tourist perceptions of the Kaibon palace are categorized as adequate in terms of the dimensions of cultural activity with a total score of 3.29.